Irrationality measures for certain $q$-mathematical constants - Bundschuh, Peter; Zudilin, Wadim (MATHEMATICA SCANDINAVICA, 2007)
We prove sharp irrationality measures for a $q$-analogue of $π$ and related $q$-series, and indicate open problems on linear and algebraic independence of the series that might be viewed as $q$-analogues of some classical mathematical constants.